ASEAN cultural heritage textile weaving from loom to computer (the Museums Association of Malaysia and Geovisions Productions, 1997)
An interactive CD-ROM publication documenting the exhibition and symposium which focused on the textile, a cultural heritage common to all ASEAN member countries. Includes profiles of each member country and slideshows of exhibits from each country.